Masquerading Lethal Strongyloidiasis in A Patient with Chronic Kidney Disease: A Case Report - Neetha S. Murthy; Morubagal Raghavendra Rao; Ranjitha Shankare Gowda; A. Tejashree; Nikita Shah (Journal of Pure and Applied Microbiology)
Strongyloides stercoralis is a nematode typified by a complex replication cycle exhibiting autoinfection, parthenogenesis and a long tenacity of survival in the human host. This infection remains endemic in the humid tropical countries of the world. There exists no gold standard test for the diagnosis of this parasitic infection. However, Inability to clinch the diagnosis can prove fatal among immunosuppressed individuals. We report one such rare case of strongyloidiasis presenting as thrombocytopenic acute gastroenteritis in a patient with chronic kidney disease.